Purchase Intentions and Luxury Brands: A Study on Consumer Behaviour in Saudi Arabia - Toffaha, Nora; Al-Dabbagh, Maha Abdullah (Journal of Economic, Administrative and Legal Sciences, 2023)
In today’s rapidly evolving global landscape, understanding the role of aspirations in shaping consumer behaviour is critical, given the significant role that aspirations play in social psychology. Luxury marketing agencies recognise the importance of intrinsic and external aspirations and consider them when designing marketing campaigns. This research explores the concept of the moral, material, and functional value of luxury brands to consumers and the intrinsic and external aspirations that drive consumers’ preferences for luxury brands. Using a descriptive-analytical approach, a questionnaire was administered to 51 respondents. The study found that income is a significant determinant of consumers’ intention to purchase luxury brands, with consumers considering their monthly income when making purchasing decisions. Additionally, the study identified the search for quality as the most important intrinsic aspiration for purchasing luxury brands, while pride, exclusivity, and distinction were the primary external aspirations. These findings provide valuable insights into the motivations and attitudes of luxury brand consumers, which can inform effective marketing strategies. The research recommends consumers who have different motivations for buying luxury brands, such as merging with the group, excellence, or purchasing power, to be careful not to over-consume or overspend on luxury brands. They should also be mindful of the environmental and social impacts of their consumption choices, and try to balance their personal preferences with ethical and sustainable practices. Luxury brand marketers should be aware of the changing consumer values and attitudes towards luxury brand consumption, especially among younger generations who may not be as influenced by social status or popularity as older generations. This may require them to innovate and adapt their products and services to meet the changing needs and preferences of consumers.